Planning for success: overcoming challenges to recruitment and conduct of an open-label emergency department–led paediatric trial. Issue 3 (13th October 2020) - Roper, Louise; Lyttle, Mark D; Gamble, Carrol; Humphreys, Amy; Messahel, Shrouk; Lee, Elizabeth D; Noblet, Joanne; Hickey, Helen; Rainford, Naomi; Iyer, Anand; Appleton, Richard; Woolfall, Kerry
Abstract : Background: Key challenges to the successful conduct of The Emergency treatment with Levetiracetam or Phenytoin in Status Epilepticus in children (EcLiPSE) trial were identified at the pre-trial stage. These included practitioner anxieties about conducting research without prior consent (RWPC), inexperience in conducting an ED-led trial and use of a medication that was not usual ED practice. As part of an embedded study, we explored parent and practitioner experiences of recruitment, RWPC and conduct of the trial to inform the design and conduct of future ED-led trials. Methods: A mixed-methods study within a trial involving (1) questionnaires and interviews with parents of randomised children, (2) interviews and focus groups with EcLiPSE practitioners and (3) audio-recorded trial discussions. We analysed data using thematic analysis and descriptive statistics as appropriate. Results: A total of 143 parents (93 mothers, 39 fathers, 11 missing information) of randomised children completed a questionnaire and 30 (25 mothers, 5 fathers) were interviewed. We analysed 76 recorded trial recruitment discussions. Ten practitioners (4 medical, 6 nursing) were interviewed, 36 (16 medical, 20 nursing) participated in one of six focus groups. Challenges to the success of the trial were addressed by having a clinically relevant research question, pragmatic trial design, parent and practitioner support for EcLiPSE recruitment and research without prior consent processes, and practitioner motivation and strong leadership. Lack of leadership negatively affected practitioner engagement and recruitment. EcLiPSE completed on time, achieving its required sample size target. Conclusions: Successful trial recruitment and conduct in a challenging ED-led trial was driven by trial design, recruitment experience, teamwork and leadership. Our study provides valuable insight from parents and practitioners to inform the design and conduct of future trials in this setting.